Optimizing plant exosome isolation: a systematic review of PEG-based precipitation, ultracentrifugation, and hybrid methodologies for biomedical applications - Rika Sari Dewi; Ni Made Dwi Sandhiutami; Melva Louisa; Irandi Putra Pratomo (Faculty of Pharmacy, Universitas Pancasila, 2025)
Plant-derived exosome-like nanoparticles (PDELNs) represent a promising frontier in nanomedicine, offering natural alternatives to synthetic drug delivery systems. These membrane-bound vesicles, typically 30-150 nm in size, contain bioactive compounds and demonstrate potential for cross-kingdom communication with mammalian cells. This objective study is to evaluate PEG-based and ultracentrifugation methods, benchmark hybrid approaches, compare emerging alternatives, and assess their impact on biomedical applications. A systematic analysis of diverse studies employing comparative yield, purity, bioactivity, scalability, and complexity metrics was conducted. A systematic search of 3 databases SciSpace Deep Search; Google Scholar; MEDLINE (2016-2024) following PRISMA guidelines, 52 studies met the inclusion criteria with combined terms : ``plant exosome'' AND (``PEG precipitation'' OR ``polyethylene glycol'' OR ``ultracentrifugation'' OR ``hybrid methods'') AND ``biomedical applications''. Findings indicate that PEG-based precipitation offers higher or comparable yields with greater scalability and cost-effectiveness but lower purity due to protein co-precipitation; ultracentrifugation yields purer exosomes with preserved bioactivity yet is resource-intensive and less scalable; hybrid methods combining PEG precipitation with ultracentrifugation or size-exclusion chromatography balance yield and purity while increasing procedural complexity. Emerging techniques, such as immunoaffinity capture, enhance specificity but face limitations in plant systems. Overall, optimized hybrid protocols improve isolation quality and bioactivity retention, supporting translational potential. These insights underscore the need for standardized, scalable isolation strategies tailored to plant exosomes to advance their clinical and biomedical applications.